Langerhans cell collections, but not eosinophils, are clues to a diagnosis of allergic contact dermatitis in appropriate skin biopsies. (13th April 2016) - Rosa, Gabriela; Fernandez, Anthony P.; Vij, Alok; Sood, Apra; Plesec, Thomas; Bergfeld, Wilma F.; Billings, Steven D.
Abstract : Background: Langerhans cell collections (LCCs) and eosinophils are traditionally considered histologic clues to allergic contact dermatitis (ACD), but rigorous histologic analyses are limited. We correlated the presence of LCCs and eosinophils in skin biopsies with patch test results in patients evaluated for ACD. Methods: Charts of all patients patch tested and biopsied at one institution from 2011 to 2013 were reviewed. Biopsies had to have a diagnosis of either spongiotic dermatitis, psoriasiform dermatitis or mixed psoriasiform/spongiotic dermatitis. Various histologic parameters were assessed, including the presence of LCCs and number of eosinophils. Design: A total of 68 biopsies met study criteria. Of these, 27 (40%) had ≥1 LCC. Twenty‐one out of 27 (78%) with ≥1 LCC were patch test positive; 6 were patch test negative (22%). Of 41 cases with no LCCs, 23 were patch test positive (23/41, 56%) and 18 were patch test negative (18/41, 44%). LCCs were significantly more common in patch test positive patients (p = 0.046). Eosinophil count did not significantly differ in patch test positive and negative cases (p = 0.216). Conclusion: LCCs are significantly more common in patch test positive cases. There were no differences with regards to presence of eosinophils between patch test positive and negative groups.